Virological outcomes of antiretroviral therapy and its determinants among HIV patients in Ethiopia: Implications for achieving the 95-95-95 target. - Tegene Atamenta Kitaw; Ribka Nigatu Haile (PLoS ONE)
Background Despite significant advancements in HIV treatment, virological outcomes remain a critical issue. Ethiopia did not meet the 90:90:90 targets set for 2020, which aimed for 90% of people on antiretroviral therapy to achieve viral suppression. As the country shifts its focus toward the 95:95:95 targets for 2030-seeking to achieve 95% viral suppression among those on ART-it is crucial to deepen our understanding of viral suppression and the factors that influence it. Methods Virological suppression was examined among 410 HIV-positive individuals on ART using the EPHIA survey. The survey employed a two-stage, stratified sampling design across urban areas in nine regions and two city administrations. Data analysis was conducted with STATA version 18, and multicollinearity was assessed using variance inflation factors. A logistic regression model identified significant determinants of viral suppression, with variables having a p-value of ≤0.05 considered statistically significant in the multivariable analysis. Results The findings revealed that 364 participants (88.78%) achieved viral suppression. Key determinants of virological outcomes included a higher wealth level (AOR = 2.67, 95% CI: 1.15-6.22), the presence of active TB (AOR = 0.27, 95% CI: 0.14-0.57), hepatitis B virus (AOR = 0.20, 95% CI: 0.10-0.31), and the utilization of HIV support group care (AOR = 3.14, 95% CI: 1.35-6.30). Conclusion Viral suppression among HIV patients is 88.78%, which even falls short of the WHO's 90% target for 2020, indicating the substantial work required to achieve 95% by 2030. To improve virological outcomes, it is crucial to increase support for low-income patients, enhance management of co-infections like TB and hepatitis B, and expand access to HIV support groups for better adherence and care.